Relationships of Physical Job Tasks and Living Conditions with Occupational Injuries in Coal Miners - Bhattacherjee, A.; Bertand, J.; Meyer, J.; BENAMGHAR, L.; OTERO SIERRA, C.; MICHAELY, J.; Ghosh, Apurna; d’HOUTAUD, A.; MUR, J.; Chau, N. (National Institute of Occupational Safety and Health, JAPAN, 2007)
This study assessed the relationships of job tasks and living conditions with occupational injuries among coal miners. The sample included randomly selected 516 underground workers. They completed a standardized self-administred questionnaire. The data were analyzed via logistic regression method. The rate of injuries in the past two years was 29.8%. The job tasks with significant crude relative risks were: power hammer, vibrating hand tools, pneumatic tools, bent trunk, awkward work posture, heat, standing about and walking, job tasks for trunk and upper/lower limbs, pain caused by work, and muscular tiredness. Logistic model shows a strong relationship between the number of job tasks (JT) and injuries (adjusted ORs vs. JT 0–1: 2.21, 95%CI 1.27–3.86 for JT 2–6 and 3.82, 2.14–6.82 for JT=7), and significant ORs=1.71 for face work, not-good-health-status, and psychotropic drug use. Musculoskeletal disorders and certain personality traits were also significant in univariate analysis. Therefore job tasks and living conditions strongly increase the injuries, and occupational physicians could help workers to find remedial measures.